The interactive relationship between confidence and academic achievement as indicators of the quality of the e-learning program - Saleh, Shoeb; Ibrahim, Khaled Ahmed Abdel-Al (Research Journal in Advanced Humanities, 2025)
This study sought to study the interactive relationship between confidence and academic achievement as qualitative indicators of the quality of the electronic program. An educational program based on the Moodle platform was designed in the course "Methods of Teaching Sharia Sciences", and it was administrated to a group of students, where the variables of confidence and achievement were measured before and after the experimental intervention, and the results were compared with a control group. Adhering to the rapid technological transformations taking place in higher education, it has become necessary to reconsider the determinants of the quality of e-educational programs, not only regarding the content or the technical structure but also by focusing on the psychological and social components that contribute to the effectiveness of the digital educational process. Amongst these prominent components is confidence which represents a dynamic element that reflects the learner's willingness to engage positively in the virtual learning environment.The results showed the effectiveness of the program in increasing the level of confidence in e-learning, which was manifested in several dimensions: confidence in the system, confidence in the content, confidence in the teacher, and confidence in the safety of the learning environment, and this was positively reflected in improving academic achievement in a statistically significant method. The study also proved that confidence is not an independent variable, but rather it is an interactive variable that affects and is affected by the context of learning, and constitutes a basic structure that affects motivation, engagement and academic perseverance. The study results recommend the need to include the dimension of confidence in models, in evaluating the quality of electronic programs and in designing educational strategies that focus on developing a positive and settled relationship between the student and the digital educational system, such as immediate technical support, effective human interaction, and ensuring transparency and clarity in the course requirements. It also calls for a holistic vision of quality that is not limited to final academic performance but extends to creating a learning environment that develops confidence and supports learner autonomy and self-responsibility.